An efficient non-Lambertian organic light-emitting diode using imprinted submicron-size zinc oxide pillar arrays - Liu, S. W. (2013)
We report phosphorescent organic light-emitting diodes with a substantially improved light outcoupling efficiency and a wider angular distribution through applying a layer of zinc oxide periodic nanopillar arrays by pattern replication in non-wetting templates technique. The devices exhibited the peak emission intensity at an emission angle of 40º compared to 0º for reference device using bare ITO-glass. The best device showed a peak luminance efficiency of 95.5±1.5 cd/A at 0º emission (external quantum efficiency—EQE of 38.5±0.1%, power efficiency of 127±1lm/W), compared to that of the reference device, which has a peak luminance efficiency of 68.0±1.4 cd/A (EQE of 22.0±0.1%, power efficiency of 72±1 lm/W).